ART AND CRAFT IN THE ERA OF CREATIVE INDUSTRY IN MALAYSIA - Mumtaz Mokhtar (Ars: Jurnal Seni Rupa dan Desain, 2018)
Malaysia is targeted to become a developed county in the year 2020.  This paper aims to establish an ideology that craft is a high art creation that deals with intellectual, careful and meaningful output. In order to develop an inclusive framework about art and craft, this paper reviews the development of craft and art in Malaysia.  The epistemological discussion on the definition of art and craft will offer a fresh spectacle on art and craft as elements that can ensure the success of the creative industry. The combination of art, craft and Malay aesthetics provides more clues on how the creative industry can go about. In addition, several initiatives from Malaysia are presented due to illustrate how Malaysia engineered the country towards 2050.  Creative industries in Malaysia have a very high potential to be developed and should supported by the government as well as the private sector.  This researcher believes that active and dynamic collaboration, new media exploration, cross discipline and innovation will be the crucial issues to be considered in the development of art and craft in the era of creative industry.